AB0199 Endocan levels and subclinical atherosclerosis in patients with rheumatoid arthritis. (12th June 2018) - Tuzcu, G.; Uslu, A.U.; Tuzcu, A.; Aydogan Baykara, R.; Omma, A.; Kucuk, A.
Abstract : Background: Rheumatoid arthritis (RA) is an inflammatory autoimmune disease with unknown etiology. Accelerated atherosclerosis (AS) and AS with heart disease are among the major causes of morbidity and/or mortality in RA. Endothelial-specific molecule 1 (endocan) is a potential indicator of vascular events and is expressed in response to inflammatory mediators in endothelial cells. Carotid intima media thickness (cIMT) is used to detect early signs of AS but also progression in cardiovascular diseases related to AS. Objectives: The aim of the present study is to evaluate the relationship of serum endocan levels with RA and cIMT as a candidate marker of diseases to be used in clinical practice. Methods: The study was conducted between June 2012 and March 2013 at the Rheumatology Clinics of Necmettin Erbakan Meram Medical School, Turkey. Thirty nine 39 RA patients, diagnosed according to the 1987 criteria of the American College of Rheumatology, and 30 age-and sex-matched healthy subjects as the control group were included in this study. Results: No significant difference was detected between groups with respect to age, sex and body mass index. In the patient group the Endocan and cIMT values were found to be 14.11±3.27 ng/mL and 0.63±0.17 mm, while in the control group they were 12.10±2.92 ng/mL and 0.51±0.12 mm, the Endocan and cIMT values were significantly higher in the patient group (p=0.009 and p=0.001, respectively). Positive correlations was found between Endocan, cIMT and Disease Activity Score of 28 joints (p=0.008 and p=0.029, respectively). When assessing the endocan levels of RA patients in the study population, cut off value of 12.21 with sensitivity of 71%, specificity of 57% and p=0.012 (area under curve: 0.678, 95% confidence interval (CI) 0.555–0.805) were observed according to ROC curve analysis. Conclusions: Endocan might be a useful marker to evaluate atherosclerotic lesions in patients with RA and also to assess disease severity. Disclosure of Interest: None declared